Antioxidant effects of immunomodulators in patients with recurrent pyelonephritis - Kolesnyk, M.; Korol, L.; Stepanova, N.; Driianska, V.; Migal, L.; Savchenko, V. (Ukrainian Journal of Nephrology and Dialysis, 2018)
The purpose of our work was to investigate the effect of immunomodulatory medicines on the intensity of oxidative stress (OS), the cytokines level and the activity of renospecific enzymes in patients with recurrent pyelonephritis (rPN). Methods. A prospective, randomized, open-label study involved of 100 women aged 33.4 ± 8.8 year old. According to the sensitivity of the detected pathogens all patients received antibacterial therapy for two weeks. Along with the main course of antibiotic therapy, 25 patients were assigned Sodium nucleinate at a dose of 0.25 g 4 times per day during 14 days, 18 patients were prescribed Galavit intramuscularly 2 ml per dayfor 10 days, and 27patients were prescribed Proteflazid according to the manufacturer’s instructions. The comparison group consisted of 30 women with rPN who received antibiotic therapy exclusively.Women were screened before and after the treatment. The content of malondialdehyde (MDA), ceruloplasmin (CP), transferrin (TF) and sulfhydryl groups (SH-groups) were determined in the blood by colorimetric method. Oxidative stress index (OSI) was calculated. The concentration of interleukins (IL) -1f, -4, -8, -10, -17, tumor necrosis factor a (TNF-a), transforming growth factor f (TGF-f), monocytic chemoactive protein-1 (MCP-1) and interferon y (IFN-y) were analyzed in the blood of the women using an ELISA. To evaluate the functional state of the renal parenchyma the activity of tubular lysosome enzymes a total f-N-acetylhexosaminidase and f-galactosidase were determined in urine. Results. The use of Sodium nucleinate decreased of the OS activity by reducing MDA level (p <0.001) and increasing the concentration of CP (p < 0.03). The serum levels ofIL-4 (p = 0.007), lL-17 (p = 0.04), TGF-f (p = 0.02) and MCP-1 (p = 0.03) were decrease. The use of Galavit contributed to a statistically significant decrease in the concentration of TNF-a (p <0.001), IL-8(p <0.001), IFN-y (p = 0.001) and TGF-f (p <0.001). The administration of Proteflazid resulted in a decrease in the concentrations of IL-8 and IFN-y, with a decrease in OSI (p =0.04) compared to pre-treatment. All applied immunomodulators partially reduced the activity of renospecific enzymes markers of kidney damage. Conclusions. The use of immunomodulators in the complex therapy of patients with rPN contributes to the partial normalization of functional activity of immune system by the decreasing ofthe production ofcytokines as its mediators and the reducing ofthe OS intensity.